2012
DOI: 10.1371/journal.pone.0039738
|View full text |Cite
|
Sign up to set email alerts
|

Uric Acid Induces Renal Inflammation via Activating Tubular NF-κB Signaling Pathway

Abstract: Inflammation is a pathologic feature of hyperuricemia in clinical settings. However, the underlying mechanism remains unknown. Here, infiltration of T cells and macrophages were significantly increased in hyperuricemia mice kidneys. This infiltration of inflammatory cells was accompanied by an up-regulation of TNF-α, MCP-1 and RANTES expression. Further, infiltration was largely located in tubular interstitial spaces, suggesting a role for tubular cells in hyperuricemia-induced inflammation. In cultured tubula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
125
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(131 citation statements)
references
References 28 publications
(41 reference statements)
4
125
0
2
Order By: Relevance
“…Hyperuricemia plays a significant role in renal injury; however, the detailed mechanisms remain unclear. Uric acid induces chemokines such as MCP-1 in the kidney and cyclooxygenase 2 in blood vessels (Kang et al, 2002;Zhou et al, 2012). Recently, uric acid was found to induce renal inflammation via NF-κB signaling (Suganuma et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Hyperuricemia plays a significant role in renal injury; however, the detailed mechanisms remain unclear. Uric acid induces chemokines such as MCP-1 in the kidney and cyclooxygenase 2 in blood vessels (Kang et al, 2002;Zhou et al, 2012). Recently, uric acid was found to induce renal inflammation via NF-κB signaling (Suganuma et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…[46][47][48] UA crystals adhere to the surface of renal epithelial cells and may induce an acute local inflammatory response. 49 Interestingly, UA induces phenotypic transition of renal tubular cells suggesting a novel potential mechanism of CKD. 50 Apart from the increased risk of developing kidney stones, such effects seem to contribute to a decrease in GFR aggravated by the presence of hypertension.…”
Section: Gouty Nephropathy and Ckdmentioning
confidence: 99%
“…In experimental animals, hyperuricemia could induce endothelial dysfunction and vascular smooth muscle proliferation leading to secondary tubulointerstitial injury through reductions in GFR and ischemia. 4,10 Recent studies have also suggested that UA may act directly on renal tubules by stimulating cytokines production 26 and epithelial-to-mesenchymal transition, 13 which are key events in renal fibrosis. A primary role of UA on the renal tubules is further supported by the observation that phenotypic transition of the renal tubules in hyperuricemia occurred before the development of GFR reduction and that significant tubulointerstitial fibrosis could be ameliorated by lowering UA.…”
Section: Discussionmentioning
confidence: 99%